Knowledge and Adoption Levels of Domestic and Export Market Oriented Mango Growers of Andhra Pradesh and their Training Needs - L. M. Ahire; N. Sandhya Shenoy; P. Vijender Reddy (Journal of Agricultural Extension Management, 2025)
Considering the importance of mango cultivation in Andhra Pradesh for commercial gain, domestic usage and as an export potential, the present investigation was conducted to study the knowledge and adoption levels of the Domestic Market Oriented and Export Market Oriented mango growers of Krishna District of Andhra Pradesh and identify their training needs in the main areas of mango production technologies. Majority of the mango growers in both the categories were found to be medium level of adopters of mango production technologies. Regarding. Knowledge level, the export market oriented mango growers had a higher level of knowledge than the domestic market oriented mango growers. It was expressed by both the categories of mango growers that training must emphasize on pest management, diseases management and selection of varieties I hybrids and grafts. The export market oriented mango growers specifically felt that the "pre and post harvest technologies" were an important component in training for ensuring better shelf life and quality of fruits to fulfill export norms. These areas may be covered in training programmes for mango farmers to bridge the gap between the knowledge and adoption levels for higher yields and improved quality production of mango